An extension of the internal/external frame of reference model: A response to Bong (1998) - Marsh, H; Yeung, A (2001)
Bong (1998) extended the internal/external frame of reference (I/E) model by attempting to operationalize the internal and external comparison processes that are central to the model and expanding the range of academic self-concept domains. Bong concluded that the "I/E model failed to receive clear support" (p. 102) in relation to predictions that she derived from her extension of the original model. Our critical evaluation and reanalysis, however, reveals problems in the operationalization of the internal and external comparisons, the rationale for post hoc confirmatory factor analysis models and, thus, the original conclusions. Our reanalysis, however, provide strong support for the original I/E model, some support for the separation of the internal and external comparison processes, and good support for a new extension to incorporate a wider range of academic domains. In particular, for these largely Hispanic-American students, Spanish achievement and self-concept were very distinct from achievements and self-concepts in all other school subjects. Accomplishments in Spanish provided one basis for evaluating accomplishments in other school subjects. In contrast, achievements and self-concepts in these other school subjects could be explained in terms of higher-order Verbal achievement and self-concept factors and higher-order Math achievement and self-concept factors.